2012
DOI: 10.1007/s10457-012-9564-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethephon: a tool to boost gum arabic production from Acacia senegal and to enhance gummosis processes

Abstract: Gum arabic production from Acacia senegal is lower in sub-humid areas than arid areas. Water stress is thought to be the reason for higher yields in arid areas. The application of ethephon is thought to mimic the effect of water stress in other plants. The objective of this study was to determine if the application of ethephon would increase the gum yields of Acacia senegal under sub-humid conditions in Cameroon. Trees receiving 40 or 120 mg ethephon were compared to controls in field experiments at a semi-ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…Gum yield was significantly ( p ¼ 0.034346) enhanced by increasing the concentration of Ethephon. These results are in line with the findings by Bhatt and Ram Mohan (1990) in India who also reported increased gum yield with increased Ethephon concentration up to 960 mg/tree, but contradict results from a recent study in northern Cameroon by Abib et al (2013) who reported low yield with higher concentration (120 mg/tree) of Ethephon and high yield under lower concentration (40 mg/tree) of Ethephon. Further investigations are needed to find out the reasons for this discrepancy that whether it is due to other factors (climate, application technique, tree provenance?).…”
Section: Dose Of Ethephonsupporting
confidence: 85%
See 2 more Smart Citations
“…Gum yield was significantly ( p ¼ 0.034346) enhanced by increasing the concentration of Ethephon. These results are in line with the findings by Bhatt and Ram Mohan (1990) in India who also reported increased gum yield with increased Ethephon concentration up to 960 mg/tree, but contradict results from a recent study in northern Cameroon by Abib et al (2013) who reported low yield with higher concentration (120 mg/tree) of Ethephon and high yield under lower concentration (40 mg/tree) of Ethephon. Further investigations are needed to find out the reasons for this discrepancy that whether it is due to other factors (climate, application technique, tree provenance?).…”
Section: Dose Of Ethephonsupporting
confidence: 85%
“…This method, in which Ethephon is directly injected into the tree, quickly reaches the tissues involved in gum production. We consider this method to be better adapted than other methods such as brushing Ethephon after bark removal (Abib et al 2013), in which chances of loss of most of the applied Ethephon through evaporation cannot be avoided.…”
Section: Ethephon-induced Gum Arabic Exudation Technique 205mentioning
confidence: 99%
See 1 more Smart Citation
“…Improved tree fallow is one of the possible approaches (Muthuri et al, 2005;Kissi, 2011). In semiarid sub-Saharan, planting A. senegal seemed to be more adapted because of its high adaptation potential to drought and fodder generation for animal as well as wood and gum arabic (Nasreldin, 2004;Palou Madi et al, 2010;Abib et al, 2013). It can also stabilize sandy soils and restore their fertility, protecting them from erosion (Mallet et al, 2002;Harmand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in many countries, an integration of this tree in Cameroon agroforestry systems was neither significant nor documented. Former studies always focused on improving gum arabic production or commercialization (Mallet et al, 2002;Palou Madi et al, 2010;Harmand et al, 2012;Mujawamariya et al, 2013;Abib et al, 2013). Little works had concerned soil fertility restoration at the lowest possible cost through their integration in agroforestry systems (Abib et al, 2013;Mujawamariya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%